Reinstatement of customary seabird harvests after a 50‐year moratorium. Issue 1 (5th December 2014) - Jones, Christopher J.; Lyver, Philip O'B.; Davis, Joe; Hughes, Beverly; Anderson, Alice; Hohapata‐Oke, John
ABSTRACT Seabird eggs, chicks, and adults have significant value for many cultures, but delayed maturation, low reproductive rates, and ease of exploitation at breeding colonies make these species especially vulnerable to overharvest. In New Zealand, indigenous Māori placed a moratorium over the harvest of grey‐faced petrel (Pterodroma gouldi) chicks in the 1960s because of concerns about diminished returns. Over the last decade, those tribes have indicated their desire to reinstate a small customary harvest. We used recent estimates of population sizes and demographic parameters to develop population models to investigate the feasibility of reinstating a sustainable harvest of pre‐fledgling chicks from 2 island populations: Moutohorā and the Ruamāhua Islands. In the absence of harvest, our simulations predicted mean annual rates of population growth of 1.01 (95% CI 1.010–1.014) for the colony on Moutohorā and 0.983 (0.978–0.989) for the Ruamāhua Islands. The Moutohorā colony could potentially sustain a fixed‐quota harvest of up to 6, 000 chicks or a fixed‐proportion harvest of up to 30% of chicks, annually. A larger‐scale harvest would require either a very conservative fixed‐quota harvest with strict monitoring of bag limits, or a fixed‐proportion harvest with reliable ongoing monitoring of the population size. We propose that Māori authorities use a fixed‐quota system up until they develop and use either a scientific assessment or a harvester‐derived index of population change. On the basis of our simulations, in 2010, Ngāti Awa, the local tribe, harvested chicks from Moutohorā for the first time in half a century. © 2014 The Wildlife Society.